7+2s-1=9s+24-5s

Simple and best practice solution for 7+2s-1=9s+24-5s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+2s-1=9s+24-5s equation:


Simplifying
7 + 2s + -1 = 9s + 24 + -5s

Reorder the terms:
7 + -1 + 2s = 9s + 24 + -5s

Combine like terms: 7 + -1 = 6
6 + 2s = 9s + 24 + -5s

Reorder the terms:
6 + 2s = 24 + 9s + -5s

Combine like terms: 9s + -5s = 4s
6 + 2s = 24 + 4s

Solving
6 + 2s = 24 + 4s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-4s' to each side of the equation.
6 + 2s + -4s = 24 + 4s + -4s

Combine like terms: 2s + -4s = -2s
6 + -2s = 24 + 4s + -4s

Combine like terms: 4s + -4s = 0
6 + -2s = 24 + 0
6 + -2s = 24

Add '-6' to each side of the equation.
6 + -6 + -2s = 24 + -6

Combine like terms: 6 + -6 = 0
0 + -2s = 24 + -6
-2s = 24 + -6

Combine like terms: 24 + -6 = 18
-2s = 18

Divide each side by '-2'.
s = -9

Simplifying
s = -9

See similar equations:

| 4(x+1)+5(x+6)= | | 9x-6(-2x+1)=-6 | | 8(2-x)=-16 | | y=-8x^9-7 | | 9/5x=1 | | 6(-x-5)=12 | | 7h-(6+9h)=8 | | -(j+9)=15 | | x/3-2=16 | | 2(3+x)=10 | | 2y-6y+8=6y+6y | | 3n+9n=108 | | (2x^2-9x-5)/(4x^2+2x^2)=0 | | ln(20)=ln(x+1)-ln(13) | | 6x+9x= | | -4xwhatnumber+16=-116 | | y^2+3x=(-2) | | x+3(x+1)=2[x-2(x+2)]-3 | | 8-4x=24+2x | | 3b-(6-b)=22 | | 4x^2+2x^2=0 | | x^2-3y-4=0 | | y=2-5x | | 2p+4=6p-3 | | 4(5x-3)=30 | | 4x^2+2y^2=12 | | 2w=4-1/2(x+6) | | 9+x^2=36 | | 5(10-1)= | | 72/9+7= | | (43+62+57+2)/3 | | 3p+2+3p=5+15 |

Equations solver categories